History of Foreign Studies of Organophosphate Induced Delayed Neuropathy - V. A. Inozemtsev; I. A. Nelga; I. V. Medvetsky; S. A. Komissarenko; A. V. Zlobin; S. V. Tretyakov; A. V. Sherstyuk (Вестник войск РХБ защиты, 2020)
Сertain organophosphates are highly toxic and can be used as chemical warfare agents. However, some classes of organic phosphorus compounds can cause so-called delayed neurotoxicity. Since the discovery of this phenomenon in 1899, extensive research has been conducted on delayed neurotoxicity caused by organophosphates. Mass poisoning of residents of the United States and Morocco in the last century demonstrated the high danger of substances that cause neurotoxicity, and gave a powerful impetus to research into this phenomenon. In addition to delayed effects, some phosphorus compounds potentiate the action of already known chemical warfare agents, increasing their toxicity by more than 10 times. Research in this direction is conducted under the auspices of the defense departments of the United States, Canada and the Netherlands. The wide distribution of phosphorus compounds in various industries and agriculture, the long hidden period and the irreversibility of lesions caused by neurotoxic organic phosphorus compounds, cause their potential threat to the security of the Russian Federation.